Tribological behaviour of TiB2-HfC ceramic tool material under dry sliding condition. Issue 12 (15th August 2020) - Jinpeng, Song; Shaowei, Liu; Ahmad, Rafiq; Jiaojiao, Gao; Ming, Lv
Abstract: In order to disclose friction and wear mechanism of TiB2 -HfC ceramic, tribological behaviour of TiB2 -HfC ceramic sliding against YG8, 316 stainless steel (316) and TA2 were investigated. Friction coefficients between TiB2 -HfC ceramics and these materials decreased not only with an increase of sliding speed but also with an increase of normal load, respectively. Wear rates of TiB2 -HfC ceramics sliding against these materials increased with an increase of sliding speed as well as with an increase of normal load, respectively. B2 O3, TiO2 and HfO2 formed in TiB2 -HfC ceramics sliding against these materials. In addition, intergranular and transgranular microcracks and WO3 appeared in the worn surface after the ceramic slid against YG8; lamellar structures like fish scale, areas of exposed grains, pits, Fe x O y and Cr2 O3 existed in the worn surface after the ceramic slid against 316; ribbon-like structures, areas of exposed grains, wear particles and furrows existed in the worn surface after the ceramic slid against TA2. Besides oxidation wear, abrasive wear played an important role in TiB2 -HfC ceramic sliding against YG8, while adhesive wear and abrasive wear played a dominant role in TiB2 -HfC ceramic sliding against 316 or TA2.